Implementación de la contabilidad para la empresa “Credi Loja” de la ciudad de Loja, periodo julio de 2013 - Silva Vivanco, Verónica Mercedes (2014)
The present thesis entitled IMPLEMENTATION OF ACCOUNTING FOR BUSINESS "CREDI Loja" Loja CITY, PERIOD JULY 2013, allowed to implement the knowledge acquired during the years of study in the race of Accounting and Auditing, fulfilling the requirement required for the degree of Engineer in Accounting and Auditing, Public Accountant-Auditor. The implementation of the accounting CREDIT Loja, I made in order to have a proper financial accounting and timely process to be one of the main objectives of the research; this could make it through the organization of documents, creation of the Initial Inventory of all rights, assets and liabilities held by the company based on the physical realization and documentation. Likewise Plan and Manual accounts for the proper handling of each of the accounts involved in the accounting process is developed, and performing auxiliary records that support revenue expenditure providing registration information in the general journal. And the accounting process was run from baseline to the financial statements for the period July 2013 thus fulfilling all the objectives for this research work. Upon completion of this work was obtained as a conclusion, that during the period July 2013, obtained gain in economic activity, for which it is recommended to keep accounts according to what implemented so that you can have good control of your business.